Ambivalent sexism, stereotypes and values in military population - Zubieta, Elena (2011)
The increasing presence of women in the public sphere has provoked cultural changes that affect social cognition. These changes implicate social organizations such as the Military. Focusing the interest in approaching modern forms of prejudice in terms of gender inequalities, we studied ambivalent sexism attitudes, values and social dominance orientation in a sample of 238 males and females from the National Military School training to become officials. Results show the presence of sexist attitudes. In sex roles and gender typing, female participants show an androgynous stereotype probably related to the need to present themselves closer to men in order to assume leadership.